Introducing anthropology - Pountney, Laura (Polity, 2015)
Introducing Anthropology is the first book of its kind. It offers a serious but accessible introduction to anthropology and is the perfect starting point for anyone new to the subject. Across a series of fourteen chapters, it addresses the different fields and approaches within anthropology, covers an extensive range of themes, and emphasizes the role of anthropology in the world today.